VALIDATION WITH SPECIALISTS OF AN INSTRUMENT TO CLASSIFY THE COMPLEXITY OF ACUTE AND CHRONIC WOUNDS - Bezerra Carvalho, Tatyelle; Sampaio, Luis Rafael Leite; Paulino da Silva, Felipe; Oliveira da Silva, Ana Caroliny; Alves de Alencar Oliveira, Vinícius; Dantas, Tays Pires; Silva, Fernanda Maria; Pinheiro, Woneska Rodrigues (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To validate the construction of a scale to classify the degree of complexity of acute and chronic wounds. Methodology: Methodological study developed in: situational diagnosis of the literature in search of instruments that classify injuries due to pregnancy signs, bibliographic research, construction of the scale and content validation of the scale with twelve judges. The Microsoft Power Point 2013 program was used to construct the technology, the snowball technique with 12 judges with expertise in the thematic area of acute and chronic injuries for validation. Results: The concordance rate among judges was considered to be greater than 0.80, for validation, the scale presented a global content validity index (CVI) of 0.99, presenting a great index in isolation, becoming validated. Conclusion: The scale was validated in objective, structure, presentation and relevance, which makes it possible to be an instrument that will contribute to the public and private system.